Narrativa econômica no Youtube: oportunidades de transformação - Rodrigues, Júlia Zillig (2020)
This research aims to discuss the economic narrative techniques practiced on YouTube and to point out new perspectives on the information worked on in this segment by the media. To this end, the corpus was analyzed from the content of the most liked video of the year 2019 from the channels Me Poupe !, by the presenter Nathalia Arcuri; O Primo Rico, by presenter Thiago Nigro; and that of presenter Gustavo Cerbasi. The methodology adopted to work on its scope was theoretically based on the authors Gaskell and Bauer (2004), Assis and Bulhões (2015) and Fiorin (2006). Then, a theoretical basis was made that reinforces this analysis and discussion. The conclusion of this work is that, the personal services / finance journalism practiced by these channels has become a great storehouse of opportunities for traditional economic journalism, providing new ways to make the language more simplified and closer to the readers, through informality , proximity, didacticism and fragmentation, rejuvenating its content and adopting new approaches